THE SCHOOL AMINISTRATION TOWORDS DIAMOND LEVEL OF HEALTH PROMOTING SCHOOL UNDER THE PRIMARY EDUCATIONAL SERVICE AREA OFFICES IN UDON THANI PROVINCE - Singhadecha, Thanakit; Chompuwiset, Patcharin; Phongphinyo, Phongnimit (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2025)
This research aimed to: 1) study the administrative components of educational institutions towards becoming Diamond Level Health Promoting Schools, and 2) study the administrative process of educational institutions towards becoming Diamond Level Health Promoting Schools. The research employs a qualitative research methodology using multiple case studies of 2 schools: 1) Ban Tha Som School and 2) Ban Sra Ku School under the Office of Primary Education in Udon Thani Province. The research process is divided into 2 stages: Stage 1 involves studying the administrative components towards becoming Diamond Level Health Promoting Schools, and Stage 2 involves studying the administrative process towards becoming Diamond Level Health Promoting Schools. The informant group consists of 16 participants involved in the operation of Diamond Level Health Promoting Schools. The research findings indicated that the study of components of Diamond Level Health Promoting Schools comprises 10 operational components: 1.1) School policy 1.2) School management 1.3) Joint projects between school and community 1.4) School environment conducive to health 1.5) School health services 1.6) Health education in schools 1.7) Nutrition and food safety 1.8) Exercise, sports, and recreation 1.9) Counseling and social support and 1.10) Health promotion for school personnel The study of the administrative process towards becoming Diamond Level Health Promoting Schools found that educational institutions operate by managing the 10 components using the Deming quality cycle (PDCA), which consists of 4 steps:2.1) Planning 2.2) Implementation 2.3) Monitoring, supervision, operational inspection, and evaluation 2.4) Summarizing and reporting operational results to lead to continuous work development in order to promote the effective implementation of the health promoting school development process.